“COSO” Internal Control Analysis on Account Receivable (Case Study in Astra Sedaya Finance Branch Cirebon) - Shella Oktavia Hermanto Putri; Dewi Kusumowati (Jurnal Manajemen dan Kewirausahaan, 2020)
The purpose of this study is to determine the internal control system of accounts receivable, and to determine whether internal control analysis of model “COSO” on Account Receivable has been implemented at PT. Astra Sedaya Finance branch Cirebon. Primary secondary data are analyzed based on the components of internal control established by the Committee of Sponsoring Organizations (COSO). The components of internal control that will be analyzed in this study, and then have 5 (five) element: 1) Control Environmental, 2) Risk Assessment,       3) Control Activities,     4) Information and Communication, and 5) Monitoring Activities. Research result Internal Control of accounts receivable at the Astra Sedaya Finance Cirebon Branch had been found effective, where the company's management had adopted the basic concepts and principles of internal control by standard operating procedures that had been set by the company. The overall system of internal control over accounts receivable at the Astra Sedaya Finance was effective enough, where management had implemented the principles of internal control in accordance with COSO, but there has been a weakness that the company still had not been put on the application system for recording and completion of documents receivable for companies in which still using manual computerized.https://doi.org/10.26905/jmdk.v8i1.4189